The Impact of Rubber Sap Price Fluctuations on The Welfare of Rubber Farmers From Islamic Economics Perspective - Dewi Sinta Ritonga; Ahmad Tarmizi; Dessy Anggraini (ILTIZAM Journal of Shariah Economics Research, 2023)
This study aims to find out how the impact of rubber latex price fluctuations on the economic welfare of rubber farmers and to find out how the Islamic economic view is about the impact of rubber latex price fluctuations on the economic welfare of rubber farmers in Sampean Village, Sungai Kanan District, South Labuhanbatu Regency. In this study a qualitative approach and the type of research approach used is descriptive, data collection method by conducting observations, interviews, and documentation. The sample technique used was non-random sampling and purposive sampling was used to determine the sample. Respondents in this study were rubber farmers. The results of this study indicate that, when there are fluctuations in the price of rubber sap, the income and economy of the community are unstable, difficulties in meeting basic needs for clothing, shelter and food, difficulties in meeting primary, secondary and tertiary needs, such as the need for children's education are hampered, difficulties to provide proper place facilities, as well as poor health because at an old age they are still working so that the level of welfare of the rubber farming community decreases. The rubber farming community earns income in accordance with the sharia economic review, which is obtained by a lawful business and this is done solely for the welfare of their lives. If viewed from Islamic principles, the rubber farming community can be said to be prosperous because they can still eat and not starve, and have a place to live. Therefore, if they are based on gratitude then they will feel well-being.   Keywords: Fluctuations, Prices and Welfare.